2019
DOI: 10.1098/rspb.2019.0359
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ability and fertility among Swedish men born 1951–1967: evidence from military conscription registers

Abstract: We examine the relationship between cognitive ability and childbearing patterns in contemporary Sweden using administrative register data. The topic has a long history in the social sciences and has been the topic of a large number of studies, many reporting a negative gradient between intelligence and fertility. We link fertility histories to military conscription tests with intelligence scores for all Swedish men born 1951-1967. We find a positive relationship between intelligence scores and fertility, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Overall, our results indicate that the primary reason that we observe low fertility among men with lower cognitive ability is because of their failure to attract a partner for stable unions for childbearing. In addition to confirming previous findings on cognitive ability and fertility in Sweden (Kolk and Barclay 2019), the findings of this study provide evidence for the importance of partnership formation, as well as showing that the intelligence-fertility association persists even after taking cumulative income into account.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, our results indicate that the primary reason that we observe low fertility among men with lower cognitive ability is because of their failure to attract a partner for stable unions for childbearing. In addition to confirming previous findings on cognitive ability and fertility in Sweden (Kolk and Barclay 2019), the findings of this study provide evidence for the importance of partnership formation, as well as showing that the intelligence-fertility association persists even after taking cumulative income into account.…”
Section: Discussionsupporting
confidence: 89%
“…In other words, for two brothers with similar income (and a shared social background), on average the brother with higher cognitive ability has more children. Previous research has shown that high and low cognitive ability is associated with the specific number of children of men in Sweden (Kolk and Barclay 2019). In particular -as highlighted in our literature review -it is plausible that much of the lower fertility of men with higher cognitive ability is affected by a reduced probability of finding a partner for childbearing.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…This is particularly true in a Scandinavian context in which more socioeconomically successful men have higher fertility (e.g. Jalovaara et al, 2018;Kolk and Barclay, 2019;Kolk, 2019). While the physiological mechanisms linking our anthropometric measures to fecundity may be universal, it is important to emphasise that the link between BMI, physical fitness, and height to socioeconomic attainment, and particularly physical attractiveness, have been shown to be socioculturally contingent (Pisanski and Feinberg, 2013).…”
Section: Introductionmentioning
confidence: 99%